Two new 1-D lanthanide selenidogermanates with the [Ge2Se6]4− anion as a bridging ligand to a lanthanide complex cation. Issue 8 (18th April 2018) - Tang, Shimei; Zhou, Jian; Zou, Hua-Hong; Liu, Xing
Abstract: Two new 1-D lanthanide selenidogermanates [ Ln 2 (tepa)2 ( μ -OH)2 ( μ -Ge2 Se6 )]n · x nH2 O ( Ln  = Tb (1 ), x  = 0.5; Ln  = Tm (2 ), x  = 0; tepa = tetraethylenepentamine) have been solvothermally synthesized and structurally characterized. Compounds1 and2 contain 1-D polymeric chains [ Ln 2 (tepa)2 ( μ -OH)2 ( μ -Ge2 Se6 )]n constructed by a [Ge2 Se6 ] 4− anion as a bridging ligand with trans terminal Se atoms linking [ Ln 2 ( μ -OH)2 (tepa)2 ] 4+ complex cations, but the stacking patterns of these neutral chains are different. The 1-D chains of1 are alternately stacked in a crossing manner, while the infinite chains of2 are arranged in a parallel manner. Although a few lanthanide selenidogermanates containing the [Ge2 Se6 ] 4− anion have been reported, their [Ge2 Se6 ] 4− anions are usually discrete. Compounds1 and2 provide the rare example of [Ge2 Se6 ] 4− anion as a bridging ligand to a lanthanide complex cation. Their optical and magnetic properties have also been studied. Abstract :